Pig‐to‐baboon liver xenoperfusion utilizing GalTKO.hCD46 pigs and glycoprotein Ib blockade. (17th March 2014) - LaMattina, John C.; Burdorf, Lars; Zhang, Tianshu; Rybak, Elana; Cheng, Xiangfei; Munivenkatappa, Raghava; Salles, Isabelle I.; Broos, Katleen; Sievert, Evelyn; McCormick, Brian; Decarlo, Marc; Ayares, David; et al.
Abstract Background Although transplantation of genetically modified porcine livers into baboons has yielded recipient survival for up to 7 days, survival is limited by profound thrombocytopenia, which becomes manifest almost immediately after revascularization, and by subsequent coagulopathy. Porcine von Willebrand's factor (VWF), a glycoprotein that adheres to activated platelets to initiate thrombus formation, has been shown to constitutively activate human platelets via their glycoprotein Ib (GPIb) receptors. Here, we report our pig‐to‐primate liver xenoperfusion model and evaluate whether targeting the GPIb‐VWF axis prevents platelet sequestration. Methods Twelve baboons underwent cross‐circulation with the following extracorporeal livers: one allogeneic control with a baboon liver, 4 xenogeneic controls with a GalTKO.hCD46 pig liver, 3 GalTKO.hCD46 pig livers in recipients treated with αGPIb antibody during perfusion, and 4 GalTKO.hCD46 pig livers pre‐treated with D‐arginine vasopressin (DDAVP) in recipients treated with αGPIb antibody during perfusion. Results All perfused livers appeared grossly and macroscopically normal and produced bile. Xenograft liver perfusion experiments treated with αGPIb antibody may show less platelet sequestration during the initial 2 h of perfusion. Portal venous resistance remained constant in all perfusion experiments. Platelet activation studies demonstrated platelet activation in all xenoperfusions, but not in the allogeneic perfusion. Conclusion These observations suggest that primate platelet sequestration by porcine liver and the associated thrombocytopenia are multifactorial and perhaps partially mediated by a constitutive interaction between porcine VWF and the primate GPIb receptor. Control of platelet sequestration and consumptive coagulopathy in liver xenotransplantation will likely require a multifaceted approach in our clinically relevant perfusion model.